“I Am Like a Lost Child”: L2 Writers' Linguistic Metaphors as a Window Into Their Writer Identity - Yang, Shizhou; Peng, Yinyin (Frontiers in Psychology, 2021)
The past two decades have witnessed a burgeoning literature on L2 writers’ identities, especially their discoursal identities. In contrast, little attention is paid to the writers’ felt sense of self when they write in an L2, which is an integral dimension of their autobiographical self. In this article, we provide empirical evidence of the nature of this aspect of L2 writer identity. To illustrate, we analyzed linguistic metaphors elicited from three groups of L2 writers (N=83), majoring respectively in Thai, Japanese, and English in a Chinese university. Statistical analysis shows that, due to challenges in content, language, organization and cultural differences, a majority of L2 writers, especial Thai and Japanese L2 writers, experience a diminishing sense of self when they write in L2. In contrast, some L2 writers, especially English L2 writers, find writing in an L2 liberating, revealing the impact of their individual learning trajectories and pedagogical practices on L2 writers’ felt sense of self. Findings suggest that L2 writers’ identity work is both complex and dynamic. L2 writing teachers can utilize the metaphor questionnaire as a tool to facilitate their learner needs analysis and to raise L2 writers’ metacognition.